How long should the pre-existing climatic water balance be considered when capturing short-term wetness and dryness over China by using SPEI? - Li, Xiuzhen; Huang, Wan-Ru (The Science of the total environment, 2021)
Short-term, fast-developing wet and dry anomalies have gained much attention, as their suddenness brings new challenges to monitoring. It is unclear how long a pre-existing climatic water surplus/deficit (defined as the difference between precipitation and potential evapotranspiration; P-PET) should be considered when monitoring short-term wetness and dryness events over China. This study aims to answer this by evaluating the performance of the daily Standardized Precipitation Evapotranspiration Index (SPEI) for different accumulation periods of P-PET in capturing sub-surface soil moisture variation over China. Our evaluations of reanalysis soil moisture from ERA5 and ERA-Interim show that ERA5 soil moisture is superior, as it is more consistent with the variation of in situ observations. Applying ERA5 soil moisture for further examination of SPEIs, we find that pre-existing conditions should be considered for different lengths of time in different regions of China because the sensitivity of soil moisture to climatic water balance is regionally dependent. For wetness, soil moisture responds to a pre-existing climatic water surplus immediately over Southeast China, but it is more delayed over North and Northeast China. For dryness, 0.5-month pre-existing water deficit conditions over Southeast China and 1.5-month conditions over the Yangtze-Huai River valley are preferable to the frequently adopted 3 months or longer. These findings highlight the length of time for pre-existing condition is shorter over wet regions, and longer over dry regions of China. This study aims to answer two questions: (1) How long should the climatic water balance be taken into account when calculating the daily SPEI in representing short-term wet and dry anomalies over China? (2) Are there differences across different climate regions? [Display omitted] •Pre-existing conditions for monitoring short-term wet/dry events are researched.•Assessment of reanalysis data in capturing soil moisture (SM) change is performed.•Sensitivity of SM to climatic water balance is regionally dependent.•Time length of pre-existing condition is shorter (longer) over wet (dry) regions.